Photoresponsive MXene/HKUST-1@CuS antimicrobial nanosheets towards efficient solar-driven water evaporation and biofilm eradication - Yingfeng Wang; Ming Huang; Maoli Yin; Wei Li; Xun Zhang; Xiaojuan Li; Gang Li (Journal of Environmental Chemical Engineering, 2026)

Regulation of air-sea CO2 flux and aragonite saturation state in coral reef ecosystems along the eastern coast of Hainan Island, China - Wei Yang; Zijia Zheng; Peiqiang Zhuang; Jianhang Zhang; Wei Deng; Shengyong Li; Yanmei Liu; Ming He; Yingfeng Chen; Bingbing Yu; Xinxin Xu; Xinxing Li; et al. (Marine Pollution Bulletin, 2026)

Long-term exposure to ultrafine particles accelerates biological aging and increases respiratory vulnerability in COPD - Yingfeng Gao; Xin Meng; Yi Zhang; Qiaoyi Hua; Ruiwei Xu; Huixia Liu; Seokho Choi; Haoyang Yao; Qianli Dong; Qi Jia; Haixia Jiang; Lijuan Wei; et al. (Journal of Hazardous Materials, 2025)

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

Liquid-mediated dense integration of graphene oxide/N-halamine aerogel microspheres with exceptional UV stability and antimicrobial activity for sewage purification - Nengyu Pan; Xiaoxing Xu; Yuting Xue; Wei Wang; Yingfeng Wang (Chemical Engineering Journal, 2025)

Carboxymethyl chitosan and poly-γ-glutamic acid-based gastroretentive sponge with high swelling and mechanical stability for targeted eradication of Helicobacter pylori - Xinyuan Zhang; Pei Xie; Yongkang Lai; Jiulong Zhao; Qiuping Gu; Yingfeng Wei; Zheng Chen; Liang Zhang; Shige Wang; Hongxin Sun; Chunping Zhu (Carbohydrate Polymers, 2025)

Seismic Prediction of Shallow Unconsolidated Sand in Deepwater Areas - Jiale Chen; Yingfeng Xie; Tong Wang; Haoyi Zhou; Zhen Zhang; Yonghang Li; Shi Zhang; Wei Deng (Journal of Marine Science and Engineering, 2025)
Recently, shallow gas fields and hydrate-bearing sand in the deepwater area of the northern South China Sea have been successively discovered, and the accurate prediction of shallow sands is an important foundation. However, most of the current prediction methods are mainly for deep oil and gas reservoirs. Compared with those reservoirs with high degree of consolidation, shallow sandy reservoirs are loose and unconsolidated, whose geophysical characteristics are not well understood. This paper analyzes the logging data of shallow sandy reservoirs recovered in the South China Sea recently, which show that the sand content has a significant influence on Young’s modulus and Poisson’s ratio of the sediments. Therefore, this paper firstly constructs a new petrophysical model of unconsolidated strata targeting sandy content and qualitatively links the mineral composition and the elastic parameters of the shallow marine sediments and defines a new indicator for sandy content: the modified brittleness index (MBI). The effectiveness of MBI in predicting sandy content is then verified by measured well data. Based on pre-stack seismic inversion, the MBI is then inverted, which will identify the sandy deposits. The method proposed provides technical support for the subsequent shallow gas and hydrate exploration in the South China Sea.

Spatio-Temporal Dynamics of Particulate Organic Carbon and Its Response to Climate Change: Evidence of the East China Sea from 2003 to 2022 - Zhenghan Liu; Yingfeng Chen; Xiaofeng Lin; Wei Yang (Journal of Marine Science and Engineering, 2025)
Particulate organic carbon (POC) plays a crucial role in oceanic climate change. However, existing research is limited by several factors, including the scarcity of long-term data, extensive datasets, and a comprehensive understanding of POC dynamics. This study utilizes monthly average POC remote sensing data from the MODIS/AQUA satellite to analyze the spatiotemporal variations of POC in the East China Sea from 2003 to 2022. Employing correlation analysis, spatial autocorrelation models, and the Geodetector model, we explore responses to key influencing factors such as climatic elements. The results indicate that POC concentrations are higher in the western nearshore areas and lower in the eastern offshore regions of the East China Sea (ECS). Additionally, concentrations are observed to be lower in southern regions compared to northern ones. From 2003 to 2022, POC concentrations exhibited a fluctuating downward trend with an average annual concentration of 121.05 ± 4.57 mg/m3. Seasonally, monthly average POC concentrations ranged from 105.48 mg/m3 to 158.36 mg/m3; notably higher concentrations were recorded during spring while summer showed comparatively lower levels. Specifically, POC concentrations peaked in April before rapidly declining from May to June—reaching a minimum—and then gradually increasing again from June through December. Correlation analysis revealed significant influences on POC levels by particulate inorganic carbon (PIC), sea surface temperature (SST), chlorophyll (Chl), and photosynthetically active radiation (PAR). The Geodetector model further elucidated that these factors vary in their impact: Chl was identified as having the strongest influence (q = 0.84), followed by PIC (q = 0.75) and SST (q = 0.64) as primary influencing factors; PAR was recognized as a secondary factor with q = 0.30. This study provides new insights into marine carbon cycling dynamics within the context of climate change.

Evaluating the impacts of drilling and extraction activities on the marine carbonate system in the natural gas fields of Beibu Gulf, Northern South China Sea - Minxia Zhang; Wei Yang; Jianhang Zhang; Chuqian Lu; Yingxu Wu; Peiqiang Zhuang; Yanmei Liu; Shasha Qi; Xing Chen; Wei Deng; Zijia Zheng; Ming He; et al. (Marine Environmental Research, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Multidimensional effects of green waste vermicomposting on cadmium contaminated soil ecosystems: From physicochemical properties to microbial communities - Li Huang; Yurui Meng; Boyou Pan; Bogui Pan; Junyu Wei; Jinhua Ding; Yingfeng Deng; Xianglan Su; Ziwei Yuan; Menghao Zhang (Journal of Hazardous Materials, 2024)

Toward the bioactive potential of myricitrin in food production: state-of-the-art green extraction and trends in biosynthesis - Yaqian Geng; Yingfeng Xie; Wei Li; Yao Mou; Fang Chen; Jianbo Xiao; Xiaojun Liao; Xiaosong Hu; Junfu Ji; Lingjun Ma (Critical Reviews in Food Science and Nutrition, 2024)

Industry 4.0 and cleaner production: A comprehensive review of sustainable and intelligent manufacturing for energy-intensive manufacturing industries - Shuaiyin Ma; Wei Ding; Yang Liu; Yingfeng Zhang; Shan Ren; Xianguang Kong; Jiewu Leng (Journal of Cleaner Production, 2024)

Large language models for diabetes care: Potentials and prospects - Bin Sheng; Zhouyu Guan; Lee-Ling Lim; Zehua Jiang; Nestoras Mathioudakis; Jiajia Li; Ruhan Liu; Yuqian Bao; Yong Mong Bee; Ya-Xing Wang; Yingfeng Zheng; Gavin Siew Wei Tan; et al. (Science Bulletin, 2024)

Genomic sequencing revealed recombination event between clade 1 and clade 2 occurs in circulating varicella-zoster virus in China - Jia Li; Dan Wang; Libin Qi; Yuewu Yang; Jiawei Pei; Yangchao Dong; Yuan Wang; Min Yao; Fanglin Zhang; Yingfeng Lei; Linfeng Cheng; Wei Ye (Brazilian Journal of Microbiology, 2024)

Integrative taxonomy in a rapid speciation group associated with mating system transition: A case study in the Primula cicutariifolia complex - Wei Zhang; Yingfeng Hu; Siyu Zhang; Jianwen Shao (Molecular Phylogenetics and Evolution, 2023)

The temporal and spatial variation of chlorophyll a concentration in the China Seas and its impact on marine fisheries - Kunlong Zhang; Xunbo Zhao; Jing Xue; Danqi Mo; Dongyu Zhang; Zhongyong Xiao; Wei Yang; Yingxu Wu; Yingfeng Chen (Frontiers in Marine Science, 2023)
Marine chlorophyll a is a key molecule for photosynthesis of marine plants and some plankton, which is important in marine ecosystems. This study utilized the chlorophyll a concentration data product observed by the MODIS sensor (MODerate resolution Imaging Spectroradiometer) to construct a long-term sequence of chlorophyll a concentration dataset by processing the raw data. Based on this, the multi-time-scale chlorophyll a concentration data was synthesized, and it was used to analyze the spatial and temporal variation characteristics of chlorophyll a concentration in China Seas. In addition, several oceanographic variables, including sea surface temperature, nutrients (phosphate, nitrate, silicate), partial pressure of seawater carbon dioxide, net primary productivity of the ocean, physical dynamics of seawater processes (mixed layer), were analyzed to ascertain their potential influence on chlorophyll a concentration. Finally, we analyzed the effects of changes in chlorophyll a concentration on marine fisheries. The result showed that: The average value of chlorophyll a concentration in China Seas from 2002 to 2022 was 0.874 mg/m 3 , with the highest concentration observed in the Bohai Sea area (4.547 mg/m 3 ) and the lowest in the South China Sea area (0.288 mg/m 3 ). The spatial variation of chlorophyll a concentration revealed an overall decrease of 0.0095 mg/m 3 in China Seas from 2002 to 2022. From the perspective of time changes, the concentration of chlorophyll a in China’s Bohai Sea area showed a downward trend from 2002 to 2022, while the Yellow Sea area showed an upward trend. The concentration remained relatively stable in the East China Sea area, whereas a significant declining trend was observed in the South China Sea area. The relationship between temperature and chlorophyll a concentration was non-linear, and chlorophyll a concentration showed some fluctuation or threshold effect with the change of seawater temperature. The three nutrient salts studied have a promoting effect on chlorophyll a, among which phosphate has the most obvious promoting effect on chlorophyll a. Chlorophyll a was negatively correlated with pCO 2 and positively correlated with ocean net primary productivity. Seasonal changes in the mixed layer had a significant effect on changes in the upper marine nutrients, which in turn affected changes in chlorophyll a concentration. Six of the eight types of algae studied show a trend toward deeper sea depths, which may have implications for the food availability of marine fish at different levels and pose new challenges for marine fisheries development.

Estimation of Gas Hydrate Saturation Regarding the Hydrate Morphology in Hydrate-Bearing Sands in the Qiongdongnan Basin, South China Sea - Deng Wei; Liang Jinqiang; Kuang Zenggui; Xie Yingfeng; Yan Pin (Pure and Applied Geophysics, 2023)

Flexural behavior of damaged RC beams strengthened with prestressed UHPC layer - Yang Zhang; Songling Huang; Yingfeng Liu; Wei Fan; Xudong Shao (Engineering Structures, 2023)

Ring-widths of Abies at tree-line ecotone reveal three centuries of early winter season temperature changes in Yunnan, China - Yingfeng Bi; Whitney Cory; Zenxin Fan; Jingchao Yang; Zhikun Wu; Wei Huang; Jianwen Li; Xuefei Yang (Climate Dynamics, 2020)
Variation in winter temperature is less well understood than in annual and summer temperatures over long timescales, particularly in low-latitude (0–30° N) montane regions with large spatial and topographic heterogeneity. Understanding these variations could be critical for forest manageemnt in these important tree growing regions. We collected tree-ring cores from Yunnan Province in montane southwest China, to determine how winter temperature has varied in the past and to explore its possible drivers in this region. Six highly correlated site chronologies were combined into a long and well-replicated regional composite (RC) chronology. The RC chronology correlated strongest with mean early winter season temperature (EWST) from November to January during 1959–2015. We applied RC chronology to reconstruct EWST from 1653 to 2015. The reconstruction shows five relatively warm historic intervals (1658–1718, 1743–1755, 1771–1791, 1929–1959, and 1995–2015) and cold intervals (1720–1742, 1792–1852, 1860–1883, 1905–1928, and 1960–1994). The 1950s with six anomalous warm seasons and 1980s with five anomalous cold seasons were the warmest and coldest decades, respectively. The EWST reconstruction generally agreed with other winter temperature reconstructions from nearby areas and with historical documents. Atlantic Multidecadal Oscillation (AMO) might be a key forcing of multidecadal winter temperature variations in montane southwest China over the past three and half centuries. Both warm and cold temperature periods coincide with respective positive and negative phases of AMO. Besides, the cold intervals during the nineteenth and twentieth centuries may also have been influenced by large volcano eruptions in low-latitude regions of south and east Asia. Our EWST reconstruction not only improves our understanding of the trends and variations of winter climate history, but also supports planning for resilience in conservation, agriculture, and forestry management in montane southwest China into the future.

DDX50 inhibits the replication of dengue virus 2 by upregulating IFN-β production - Peijun Han; Wei Ye; Xin Lv; Hongwei Ma; Daihui Weng; Yangchao Dong; Linfeng Cheng; Hesong Chen; Liang Zhang; Zhikai Xu; Yingfeng Lei; Fanglin Zhang (Archives of Virology, 2017)

Random mutagenesis and recombination of sam1 gene by integrating error-prone PCR with staggered extension process - Yingfeng An; Jianfei Ji; Wenfang Wu; Ribo Huang; Yutuo Wei; Zhilong Xiu (Biotechnology Letters, 2008)